Behavioral and biochemical changes associated with the analgesic effects of (2R,6R)-hydroxynorketamine alone and in combination with meloxicam following disk puncture in mice - Das, Vaskar; Milejczyk, Isabella; Basovich, Michael B.; Moric, Mario; Kaila, Jay; Thomas, Craig J.; Buvanendran, Asokumar; McCarthy, Robert J. (Frontiers in Pain Research, 2025)
IntroductionLow back pain affects around 619 million people globally and is the most prevalent musculoskeletal condition worldwide. Low back pain is often difficult to treat with traditional drug combinations, and opioids are prescribed for up to 60% of patients with debilitating low back pain. This study aimed at characterizing the analgesic effect of (2R,6R)-Hydroxynorketamine, an α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor dependent analgesic agent, alone or in combination with meloxicam in a murine lumbar disk puncture model.MethodsMale and female C57BL/6J mice underwent lumbar disk puncture and developed tactile allodynia. At day 7 postoperatively, mice were randomized to receive intraperitoneal saline, (2R,6R)-Hydroxynorketamine, meloxicam or both drugs co-administered for 3 consecutive days. Analgesia was assessed at baseline and 24 h following each injection using von Frey testing of both hind limbs and the area under the paw withdrawal curve (AUC0−3d) was determined. Brain, spinal cord, and dorsal root ganglion tissues were obtained for immunohistochemistry and western blot analysis.ResultsPrior to disk puncture paw withdrawal thresholds were 3.44 ± 0.51 g before surgery and were reduced to 0.54 ± 0.38 g at day 7 without a difference by sex; however, sex-specific responses were evident in other behavioral outcomes. EC50 estimates for (2R,6R)-Hydroxynorketamine were 14.2 mg/kg (95% CI: 10.3 mg/kg to 19.7 mg/kg) in male and 16.9 mg/kg (95% CI: 12.8 mg/kg to 22.3 mg/kg) in female mice (P < 0.637). (2R,6R)-Hydroxynorketamine plus meloxicam enhanced the analgesic effect on the AUC0−3d of meloxicam alone. (2R,6R)-Hydroxynorketamine analgesia was associated with increases in Glutamate receptor A1 & A2, p-Kv2.1, p-CaMKII and reduced BDNF protein ratios in the hippocampus, attenuated c-Fos in the spinal cord, and decreased BDNF at the dorsal root ganglion (DRG).DiscussionOur findings demonstrated that the analgesic benefit of (2R,6R)-Hydroxynorketamine is dose dependent, protein analysis suggests that (2R,6R)-HNK analgesic is associated with augmenting GluA1, GluA2, CaMKII, Kv2.1 and a reduction in BDNF protein ratios in hippocampus, decreased spinal cord c-Fos and reduced BNDF at the dorsal root ganglion. (2R,6R)-Hydroxynorketamine also augmented meloxicam analgesia in disk puncture mice. Our finding supports further study of the clinical potential of (2R,6R)-Hydroxynorketamine as a non-opioid analgesic for discogenic back pain.